Reputation, Status Networks, and the Art Market - L.E.A. Braden; Thomas Teekens (Arts, 2019)
The effect of an artist’s prestige on the price of artwork is a well-known, central tenant in art market research. In considering how an artist’s prestige proliferates, much research examines networks, where certain artistic groupings and associations promote individual member’s artistic standing (i.e., “associative status networks”). When considering the role of associative status networks, there are two models by which status may increase. First, the confirmation model suggests that actors of similar status are associated with each other. Second, the increase model suggests that a halo effect occurs, whereby an individual’s status increases by association with higher-status artists. In this research, we examine the association of artists through museum exhibition to test confirmation versus increase models, ascertaining whether prestige acquisition is a selection or influence process. This research capitalizes on the retrospective digitization of exhibition catalogues, allowing for large-scale longitudinal analysis heretofore unviable for researchers. We use the exhibition history of 1148 artists from the digitized archives of three major Dutch museums (Stedelijk, Boijmans-Van Beuningen, Van Abbe) from 1930 to 1989, as well as data on artists’ market performance from artprice.com and bibliographic data from the WorldCat database. We then employ network analysis to examine the 60-year interplay of associative status networks and determine how different networks predict subsequent auction performance. We find that status connections may have a point of diminishing returns by which comparison to high prestige peers increases one’s own prestige to a point, after which a high-status comparison network becomes a liability.